2022
DOI: 10.3390/jcm11143981
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Intraocular Pressure and Extraocular Muscles Based on Orbital Magnetic Resonance T2 Mapping in Thyroid-Associated Ophthalmopathy Patients

Abstract: Background: The correlation between intraocular pressure (IOP) and the magnetic resonance imaging (MRI) parameters in thyroid-associated ophthalmopathy (TAO) patients was explored. Methods: This study included 82 eyes in 41 TAO patients who had a large difference in the IOP between each eye. We measured the T2 relaxation time (T2RT) of the extraocular muscles (EOMs), the orbital fat, and the area of the EOMs. Results: There was a positive correlation between IOP and exophthalmos, the clinical activity score (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The current opinion is that IOP increase is mostly due to orbital edema, which consists of the increased production of GAGs by the orbital fibroblasts, and inflammation-activated fibroblasts differentiating into adipocytes ( 19 ). A recent study used T2RT, which reflects the edema changes caused by autoimmune inflammation and vascular congestion, and found that the high IOP in patients with TAO was positively correlated with EOM inflammation ( 13 ). This is consistent with our finding of a significant increase of EOM volume in the MRI T2 phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current opinion is that IOP increase is mostly due to orbital edema, which consists of the increased production of GAGs by the orbital fibroblasts, and inflammation-activated fibroblasts differentiating into adipocytes ( 19 ). A recent study used T2RT, which reflects the edema changes caused by autoimmune inflammation and vascular congestion, and found that the high IOP in patients with TAO was positively correlated with EOM inflammation ( 13 ). This is consistent with our finding of a significant increase of EOM volume in the MRI T2 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Proptosis, orbit enlargement, EOM proliferation, and OF expansion can be measured using orbital MRI and subsequently resolved ( 11 ). However, most of the existing studies have focused on the clinical features of orbital tissue in TAO, such as quantitation of EOM fibrosis by T1 mapping and T2 relaxation time (T2RT) ( 12 , 13 ), and the relationship between IOP and orbital tissue remains unexplored in comparison.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that as IOP increases, the trabecular meshwork expands toward the SC lumen and concurrently causes the narrowing of the lumen [ 23 ]. Moreover, several studies have observed IOP elevation in GO eyes [ 6 , 24 ]. Elevated IOP in healthy individuals has also been shown to decrease the cross-sectional area of SC [ 25 , 26 ].…”
Section: Dıscussıonmentioning
confidence: 99%